Profil Tekanan Darah dan Kejadian ESO Pasien Penerima Monoterapi Antihipertensi di Puskesmas Kabupaten Banyumas - Aulia Rahman; Luthfi Hidayat Maulana; Syaiful Prayogi (Universitas PGRI Madiun, 2022)
Hypertension is a cardiovascular disease with the highest prevalence. JNC VIII categorizes hypertension if blood pressure > 140/90 mmHg. This study aims to determine the patient's profile, blood pressure, and the possible incidence of ESO in patients receiving antihypertensive monotherapy in Banyumas Regency, the eastern region. The study was conducted retrospectively. Samples were carried out using total sampling. The sample size in this study was 44 patients. The highest number of patients was female, i.e. 82%, with the majority having primary education/equivalent. The monotherapy used was Amlodipine (class CCBs), Candesartan (class ARB), and Lisinopril (class ACEI) with the highest number of prescriptions being Amlodipine (70.5%). The incidence of ESO that is often experienced is dizziness by 6.8%. There was no significant difference in the effectiveness of each monotherapy used with Asymp. Sig = 0.666 (for systolic pressure) and 0.716 (for diastolic pressure).